The Model of Workload, Professional Competence and Performance - tan, Mulyadi; Anoesyirwan, Anoesyirwan; Zain, Yuli (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study is to explore how workload and professional competence affect teacher performance in SMP Negeri 13 Kota Bandung. The study adopted a quantitative approach, utilizing multiple regression analysis. Primary data were collected through questionnaire survey administered to 31 respondents selected through purposive sampling. The results show that workload and professional competence significantly affect teacher performance in SMP Negeri 13 Kota Bandung simultaneously or partially. Furthermore, the combined effects of workload and professional competence explained 76.3% of the variance in teacher performance, while the remaining 23.7% was due to factors unobserved in this study.